Land Use Land Cover Assessment of a Protected Area Complex in Western Terai Arc Landscape of India - Kumari , Priti; Mani, Ashish; Rana, Sakshi; Badola, Ruchi; Hussain, Syed Ainul (Indian Forester, 2025)
Kalesar National Park and Wildlife Sanctuary (KNPWLS) situated in the state of Haryana, is an important protected area in the Terai Arc Landscape (TAL), providing connectivity between Simbalbara National Park and the Rajaji National Park. Authors examined the land use land cover (LULC) of KNPWLS using supervised classification and object-based classification methods, utilizing Sentinel-2B satellite imagery with a 10 m spatial resolution. The resulting LULC classes from both methods resulted in ten classes, viz. Sal forest, mixed forest, plantation, grassland, dry riverbed, waterbodies, builtup, agriculture, agroforest and wasteland. The findings reveal higher percentage of mixed forest (50.62%), followed by Sal forest (30.78%). The accuracy assessment reveals overall accuracy by 83%, supported by 79.71% of Kappa coefficient. This study provides the first comprehensive LULC map of KNPWLS, offering valuable insights for conservation and management planning. The findings serve as a critical tool for informed decision-making, helping to guide future biodiversity conservation efforts and sustainable land use management within the smaller protected areas.